The Body Awareness Workbook for Trauma : Release Trauma from Your Body, Find Emotional Balance, and Connect with Your Inner Wisdom. - Brown Yau, Julie (Reveal Press spiritual growth workbook, 2019)
The Body Awareness Workbook for Trauma presents a comprehensive mind-body approach to healing trauma that invites readers to reconnect with their body's innate capacity for healing, growth, vitality, and joy. Readers learn to move past their trauma toward posttraumatic growth, balance their emotions, and transform the dark side of trauma into body awareness and spiritual fulfillment.